Decreased posterior cruciate and altered collateral ligament loading following ACL transection: A longitudinal study in the ovine model. Issue 3 (26th November 2013) - Atarod, Mohammad; Frank, Cyril B.; Shrive, Nigel G.
ABSTRACT Although ACL deficiency is shown to lead to joint degeneration, few quantitative data are reported on its effect on soft tissue structures surrounding the knee joint, specifically, the posterior cruciate and collateral ligaments. The kinematics of the stifle joint of sheep (N = 5) were measured during "normal" gait, as well as 4 and 20 weeks after ACL transection. These motions were reproduced using a unique robotic manipulator and the loads borne by PCL, MCL, and LCL during gait were determined. Our results demonstrated a significant decrease in mean PCL loads 20 weeks post‐ACL injury, at hoof‐strike (0% of gait, p = 0.034), hoof‐off (66% of gait, p = 0.006), peak‐swing (85% of gait, p = 0.026), and extension‐before‐hoof‐strike (95% of gait, p = 0.028). Mean MCL loads did not significantly increase following ACL transection, maybe due to large between‐animal variation. Finally, mean LCL loads indicated a significant decrease (p < 0.047) at 20 weeks across the entire gait cycle. From a clinical perspective, the load redistributions observed in cruciate and collateral ligaments following ACL injury indicate that these tissues can carry/adapt to the altered mechanical environment of the joint. The considerable variability in the magnitudes of change following ACL injury among animals also simulates clinical variability in humans after trauma. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:431–438, 2014.